KARAKTERISTIK KIMIA DAN SENSORI KUKIS BERBAHAN BAKU TEPUNG MOCAF DENGAN TAMBAHAN PUREE JAGUNG KUNING - Raya, Indah; Augustyn, Gelora; Lopulalan, Cynthia (MARSEGU : Jurnal Sains dan Teknologi, 2024)
Mocaf (Modified Cassava Flour) is flour from modified cassava. Mocaf flour has a high carbohydrate content so it is necessary to add other nutritional sources to enrich the product produced. Corn puree is an alternative for producing cookies with high nutritional value. The aim of this research was to determine the best concentration of mocaf cookies with the addition of sweet corn puree. The parameters tested are proximate and sensory tests. The design used was a Completely Randomized Design (CRD) with 1 factor, namely the concentration of corn puree. The analysis results obtained were that the treatment of adding sweet corn puree (20%) was the best addition of sweet corn puree. The chemical test results were water content 1.96%, ash content 2.24%, fat content 17.95%, and protein content 4.34%. In contrast to the carbohydrate content, the best treatment for sweet corn puree (0%) is the carbohydrate content of 77.22%. The results of the sensory test showed that the panelists showed a tendency to like the research cookies.